Problems of Multidisciplinary Regulation of Confiscation of Property in Ukraine in the Conditions of European Integration Processes - Yurkevych, Yurii M.; Krasnytskyi, Ivan V.; Krupnyk, Roman V.; Hrushchynska, Nataliia I.; Petronchak, Yuliia O. (International Journal of Criminology and Sociology, 2021)
This study provides a detailed theoretical analysis of problems of regulation of confiscation of property in Ukraine in different branches in the conditions of European integration processes. Property relations are the object of protection of various branches of law: constitutional, civil, administrative, criminal, etc. Accordingly, the regulation of property relations by the provisions of both public and private branches of law often gives rise to numerous discussions about certain social relations within this institution. In the national law of Ukraine confiscation is considered both as a ground for termination of property rights, as a special civil law method of protection of copyright and related rights, as a type of administrative penalties (including for violation of customs and tax legislation), as an additional type of criminal penalties, and as a special procedure in criminal proceedings. Proper legal provision of confiscation is a prerequisite for recognising Ukraine as a reliable partner of the European and world community. According to the results of the study, the position regarding the prospects of research and improvement of regulation of property confiscation in the modern market economy was outlined.